Queen of myth and monsters - St. Clair, Scarlett (St. Clair, Scarlett. Adrian x Isolde, 2023)
"Isolde, newly coronated queen, has finally found a king worthy of her in the vampire Adrian. But their love for each other has cost Isolde her father and her homeland. With two opposing goddesses playing mortals and vampires against one another, Isolde is uncertain who her allies are in the vampire stronghold of Revekka. Now -- as politics in the Red Palace grow more underhanded, inexplicable monster attacks plague the villages, and a deadly crimson mist threatens all of Cordova -- Isolde must trust in the bond she's formed with Adrian, even as she learns troubling information about his complicated past." --